(untitled) (American Journal of Islam and Society, 2001)
The problem that confronts scholars who intend to engage in organizing issues associated with the environment in a manner that is logical and coherent is that many of those issues are conceptually overlapping, territorially interrelated, and academically multidisciplinary. Added to this are the submerged and not so submerged tensions between environmentalism on the one hand, which restrains the frontier exercise of human power and control over natural resources, and neoliberali.sm on the other, which ordinarily considers such limitations oddities. Many of the scholars who have been successful in this endeavor have tried to focus on related environmental mediums, issues, or regions. Despite its wider scope, Environmental Politics: Domestic and Global Dimensions, which is in its third edition, weaves through the maze of topics it covers using a process perspective. The book focuses on formal and informal institutions and processes in trying to develop an understanding about how global environmental policies are developed in the United States. It is essential to note from the outset that the domestic and global dimensions of the book basically focus on the United States’ responses to those challenges and, accordingly, a foreign reader may read into the title: The US. Environmental Politicr: Domestic and Global Dimensions. The author, Dr. Jacqueline V. Switzer, does not waste any time in letting the reader know that the approach to the book is through the process model, a process whereby the Congress, the president and his executive branch, and the judiciary jostle for influence in formulating, implementing or redirecting environmental policies (p. viii). An associate professor of political science at Northern Arizona University, the author deploys her understanding of the history, process, and conflicting interests that have shaped the United States’ environmental policies both at home and at the international plane, to organize the complex issues covered in the book. The third edition is remarkable for carefully updating a book that is reputed to be an information powerhouse regarding environmental policy, actors, disputes, and processes, up through the final years of the Clinton administration. It also incorporates, in each chapter, a global dimension of the main topic of the chapter, and it revises the "Another View, Another Voice" boxes of each chapter ...